Prevention and early treatment of driveline infections in ventricular assist device patients: the DESTINE staging proposal and the first standard of care protocol - Bernhardt, Alexander; Schlöglhofer, Thomas; Lauenroth, Volker; Müller, Florian; Müller, Marcus; Schoede, Alexandra; Klopsch, Christian (Journal of critical care, 2020)
Mechanical circulatory support (MCS) using left ventricular assist devices (LVAD) have considerably improved the quality of life and survival rate of patients with end-stage heart failure. Despite substantial technological progress, major challenges with regard to VAD-specific and VAD-related infections have hitherto hindered the broader application of this promising therapy approach. Driveline infections (DLI) range among the main adverse events experienced in LVAD patients. However, many centers still apply their own protocol for driveline exit site (DLES) care and an international standard on prevention, reduction and early treatment of DLI after the perioperative period has not yet been defined. In March 2019, VAD coordinators and cardiac surgeons from Germany and Austria met to develop a standard of care procedure (SOP) as well as a new staging approach with recommended actions for treatment of VAD carriers. In this Driveline Expert STagINg and carE (DESTINE) study group we developed a 10-step SOP for DLES care with emphasis on essentials such as clean and save preparation, sterile dressing change and secure driveline immobilization. An advanced wound staging approach was defined with recommended actions for prevention, early detection and stage-related management of DLI. Broad consensus was reached on the fact that an interdisciplinary approach both in DLES care and DLES healing disorder awareness is required to prolong infect-free survival times on MCS as well as to ensure high patient compliance and quality of life. In conclusion, a new detailed SOP for appropriate DLES care and an advanced wound staging approach for prevention and management of DLI were defined on an expert level applicable for VAD clinicians, practitioners and care givers in Central Europe.
Available online 17 December 2019
Gesehen am 07.04.2020